How does social media use enhance employee's well-being and advocacy behaviour? Findings from PLS-SEM and fsQCA - Rahul Bodhi; Yatish Joshi; Anurag Singh (Acta Psychologica)
Despite the extensive use of social media in workplaces, the implications of social media usage in organizational contexts such as employee advocacy and well-being have yet to receive significant attention from a research assertion. Thus, utilizing the conversation of resource theory, the current study analyses the relationship between work-related social media use and social-related social media use and employee advocacy behaviour. Moreover, it examines the mediating role of employee's psychological well-being and social well-being. An online survey was conducted to collect data based on a cross-sectional design. A total of 302 valid responses were collected from employees from the knowledge-intensive service industry. The PLS-SEM results indicated that work-related social media use and social-related social media use positively affect employee employee's psychological well-being and social well-being, whereas social-related social media use is positively associated to employee advocacy. Additionally, social well-being also positively affects employee advocacy. The mediation analysis also revealed that social well-being partially mediates the relationship between social-related social media use and employee advocacy, as well as work-related social media use and employee advocacy. The results obtained from fuzzy-set qualitative comparative analysis (fsQCA) showed that different configurations, such as “∼Work-related social media use ∗ Social well-being”, “Work-related social media use ∗ Social-related social media use”, “Social-related social media use ∗ Psychological well-being”, and “Psychological well-being ∗ Social well-being”, generated high employee advocacy.